The Bethesda handbook of clinical oncology - Abraham, Jame; Gulley, James L. (James Leonard), 1964- (Philadelphia, PA : Wolters Kluwer, 2010)
"The Bethesda Handbook of Clinical Oncology is a clear, concise, and comprehensive reference book for the busy clinician to use in their daily patient encounters and for board review. The book has been compiled by clinicians who are working at the National Cancer Institute, National Institutes of Health, Cleveland Clinic, M.D. Anderson, Mayo Clinic as well as experts from other academic institutions. To limit the size of the book, less space is dedicated to etiology, pathophysiology, and epidemiology and greater emphasis is placed on practical clinical information. For easy accessibility to the pertinent information, long descriptions are avoided, and more tables, pictures, algorithms, and phrases are included. The Bethesda Handbook of Clinical Oncology is not intended as a substitute for the many excellent oncology reference textbooks available that are essential for a more complete understanding of the pathophysiology and management of complicated oncology patients. We hope that the reader-friendly format with its comprehensive review of the management of each disease with treatment regimens, including dosing and schedule, makes this book unique and useful for hematology/oncologists, advanced practice providers, hematology and oncology fellows, residents, students, oncology nurses, and allied health professionals"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Neoplasms; Handbook